From Exception to Promotion Re-Thinking the Relationship between International Trade and Environmental Law - Cima, Elena (International Environmental Law, 2021)
From Exception to Promotion: Re-Thinking the Relationship between International Trade and Environmental Law tells a new, unconventional story of the relationship between international trade and environmental law, where the keyword is synergy rather than conflict, and where sustainable development and environmental protection are portrayed as part of the very nature and purpose of the trade regime.; Readership: Academics and students interested in international trade and environmental law, as well as in the interface between different areas of international law.